Strength Prediction Model of a Particle-Reinforced Shellproof Ceramic Composite - Ni, X.H.; Chen, C.; Liu, X.Q.; Zhang, S.Q. (Проблемы прочности, 2014)
On the basis of the microstructure of particle-reinforced
shellproof ceramic composite, and the
intergranular fracture feature, a dislocation
pile-up fracture model of the small-particle ceramic
composite is developed, the mechanism
of formation, growth and coalescence of
microcracks. The complex effect of the small
particle pull-out and large particle cracking is
concerned, when constructing the crack extension
fracture model. Thereafter, the influence of
particles’ volume fraction and matrix grain diameter
on fracture strength is studied. The experimental
data shows that the proposed strength
prediction model is successful and can be
generally applied. На основе микроструктуры пуленепробиваемого керамического композиционного материала,
упрочненного мелкими частицами, и характера его внутрикристаллического разрушения
разработана модель разрушения при скоплении дислокаций, т.е. исследован механизм образования, роста и слияния трещин. При разработке модели разрушения при распространении
трещины учитывали совместное влияние процессов выкрашивания мелких частиц и растрескивания крупных частиц. Изучено влияние относительного объема частиц и диаметра матричного зерна на сопротивление разрушению. Экспериментальные результаты показали, что
данная модель прогнозирования прочности является эффективной и общеприменимой. На основі мікроструктури куленепробивного керамічного композиційного матеріалу,
зміцненого дрібними частинками, і характеру внутрішньокристалічного руйнування
розроблено модель руйнування при скупченні дислокацій, тобто досліджено механізм виникнення, росту і злиття тріщин. При розробці моделі руйнування при
розповсюдженні тріщини враховували спільний вплив процесів викришування дрібних частинок і розтріскування великих. Вивчено вплив відносного об’єму частинок і
діаметра матричного зерна на опір руйнуванню. Експериментальні дані показали, що
запропонована модель прогнозування міцності є ефективною і загальновживаною.